A Socialised Medical Service (London : The Socialist Medical Association, 1933)
1933 1933 1930s 21 pages their patients' home or occupation to the Sanitary or Industrial Health Officials. At least one of the Home Doctors in each unit should be a woman. In the Health Centres specialists of all kinds (including those for Tuberculosis and Venereal Disease) will see by appointment the patients referred to them by the Home Doctors. These specialists will also visit patients in their homes when unfit to attend at the Health Centre. In the Health Centres the Medical Records will be kept and health education by lecture and demonstration will be carried out. There will also be departments for Child Welfare, Remedial Exercises, Light Treatment and X-rays, as well as Clinics for the study and treatment of early mental disease. In the Health Centres dispensing will be carried out by qualified pharmaceutical chemists. The ante-natal clinics staffed by specialists will also be situated in the Health Centres, and the reports from these and all other departments will be sent to the Home Doctors concerned as well as being entered in the Medical Records. From the Health Centres the District Nurses and Health Visitors will carry out their duties. (b) In Rural Districts the numbers in the units of population served by each Health Centre will be slightly smaller, and attached to these centres in outlying districts will be clinics with two to four Home Doctors attached to each. These doctors will see their patients in these clinics instead of in the Health Centre, but will send on their patients to the Health Centres for specialist treatment. The Home Doctors in County Districts will be responsible for the health of 2,000 instead of 2,500 people. The Dental Service All available evidence points to the fact that from the health point of view constant dental supervision does really pay. It must be admitted, however, that dental problems not infrequently arise, the solution of which is by no means easy, and dental consultations are, therefore, necessary in many cases if the best results are to be obtained. Fortunately we may expect a considerable development of our road transport system in the near future, so that the connections between towns and villages will probably be a great deal better than they are at present. Consequently while it will be useful for a dentist to attend at stated intervals at the outlying clinics, most of the dental work of the future will be carried out in fully equipped dental clinics in the Health Centres and Hospitals by full-time dentists assisted by dental mechanics and clerical assistants. In charge of each of these dental clinics will be a dentist of experience, preferably with a medical qualification. It will be the business of the other dentists before undertaking a line of treatment in all but the 10 292/847/1/1